Wind Tunnel Designs and Their Diverse Engineering Applications - Ahmed, N. A. (IntechOpen, 2013)
This book is intended to be a valuable addition to students, engineers, scientists, industrialists, consultants and others providing greater insight into wind tunnel designs and their enormous research potential. It is a compilation of works from world experts on subsonic and supersonic wind tunnel designs, applicable to a diverse range of disciplines. The book is organised in two sections. The first section comprises of three chapters on various aspects of stationary and portable subsonic wind tunnel designs, followed by one chapter on supersonic wind tunnel and the final chapter discusses a method to address unsteadiness effects of fan blade rotation. The second section contains four chapters regarding wind tunnel applications across a multitude of engineering fields including civil, mechanical, chemical and environmental engineering.